Ports 2022. papers from sessions of the 16th triennial international conference, September 18-21, 2022, Honolulu, Hawaii - Erbland, Philip, J.; Jones, Bryan N. (American Society of Civil Engineers, 2022)
This collection contains selected papers from the 16th Triennial International Conference, held in Honolulu, Hawaii. Ninety-two papers are included in this volume on the following topics: climate change and coastal resilience; dredging and dredged material; environmental remediation; wildlife habitats; equipment and systems; landside connections; navigation and waterways; sustainability and asset management; project delivery; and terminal design. These papers will be of interest to practitioners, researchers, and all stakeholders working in port planning and development.